The Environmental Impact of Changes in Cow Productivity and Its Component Traits in South Africa's Landrace Beef Breeds - Jordaan, Frans J.; Neser, Frederick W. C.; Maiwashe, Azwihangwisi; King, Zelda; Scholtz, Michiel M. (Frontiers in Animal Science, 2021)
Any reduction in the carbon footprint of beef production will contribute to future sustainability. This study investigates the environmental impact (carbon footprint) of the changes that occurred in cow productivity in the cowherds of four South African landrace breeds over a period of 25 - 30 years. Cow productivity, defined as kilogram calf weaned per large stock unit mated, increased by 18.3%, 10.0%, 14.2% and 10.4% in the Afrikaner, Bonsmara, Drakensberger and Nguni, respectively. This resulted in a decrease in the carbon footprint, as defined by the enteric methane emissions factor, of between 6.6% and 12.0%. Changes in the cow productivity component traits, viz. weaning weight, cow weight and fertility (as measured by inter-calving period) was also investigated. In all breeds, except the Nguni, the change in the environmental trends were less than that of the direct genetic or phenotypic trends. The genetic trends for direct weaning weight in the Afrikaner, Bonsmara and Drakensberger were +6.7 kg, +11.7 kg and +6.2 kg, respectively. In the case of the Bonsmara and Drakensberger breeds, the genetic trends were larger than the phenotypic trends, which may indicate that the environment cannot support the higher “genetic” weaning weights. The genetic trends for mature cow weight in Bonsmara and Drakensberger were +15.9 kg and +15.1 kg, respectively, whereas in the Afrikaner and Nguni it was not significantly different from zero (R2 ≤ 0.24). The trends in the phenotypic mature cow weights were -8.3 kg, +17.5 kg, +8.5 kg and -17.2 kg for in the Afrikaner, Bonsmara, Drakensberger and Nguni, respectively. Although the observed inter-calving period of all breeds declined, there was no genetic change in inter-calving period for any of the breeds. It is proposed that selection indices are developed for cow productivity, which can be extended to a carbon footprint selection index. It is recommended that similar studies be done on all the major beef breeds in South Africa, especially those that rely on regular importation of genetic material.